Children's 1000 Words Picture Dictionary - Qardi, Noorullah and Memon T.A.; Illustrated by: Sumera Kamran (Karachi, Pakistan Children publications, 2004)
A beginner's dictionary gives simple definitions of more than one thousand commonly used words and helps young readers develop vocabulary, spelling, and alphabetizing skills. BOMC Main.
Colour Illustration
Keywords: Picture dictionaries, English